User Interface Analysis of Gapura Universitas Multimedia Nusantara Website - Dara Shafira Zahra; Wella Wella; Aditya Satyagraha (ULTIMART Jurnal Komunikasi Visual, 2021)
The user interface (UI) of the Gapura site is proven to have various problems such as a poor visual hierarchy, UI that confuses its users, and UI that are considered unattractive by users. These things result in the poor feedback of its users. This study aims to examine the problems in the Gapura site by using the guidelines of the e-book published by UXPin, "Web UI Best Practice". The series of tests that will be conducted are blur test, scenario test, questionnaire and survey. After that, a prototype will be built according to the results of the tests with the aim of improving the UI Gapura site. The results of the prototypes made show that while there are still mistakes regarding the visual hierarchy of the prototype, the prototype was proven to be more usable by the users, and received better feedback than the Gapura site. Thus, it can be concluded that the changes applied in the prototype has made the UI of Gapura better. Keywords: user interface; uxpin; web ui design; web ui prototype; ui evaluation